(untitled) (Heteroglossia – studia kulturoznawczo-filologiczne, 2019)
The study of dynamic codes in various social and legal conditions and the problems of agnonymy in intercultural communication allow us to automatically assert that collective memory and a common past are the basis of socialism, language, as a true chronicler, records everything in its linguistic picture of the world. The informative value of a communicative unit is determined not only by its correlations with a specific denotate, but also by the specific emotional-aesthetic attitude of native speakers towards it, which are uniform manifestations in a given linguistic and cultural community. The scientific and technological revolution accelerates the processes leading to agnonymy (dynamics of vocabulary and connotative meanings, dynamics of printed forms, urban palimpsests, text modifications, etc.).